Tratamento de efluente secundário de estação de tratamento de esgoto contaminado com metilparabeno por processos baseados em ozônio - Antonio Kaique Cantto (2022)
ABSTRACT The presence of parabens and other emerging pollutants (PEs) in wastewater is a reality that should be studied and discussed by agents involved in the environmental and sanitation areas, given their potential risks to human health and natural ecosystems. The understanding of these new pollutants is necessary for the development and improvement of effective treatment technologies, since the current processes are not able to remove them. Researchers around the world are studying and betting on Advanced Oxidative Processes (AOPs), such as ozonation, as one of these solutions. Thus, this study was dedicated to the degradation of methylparaben (MeP) in sanitary effluent through the ozone-peroxide (O3/H2O2) process, using experimental planning as a tool to select and optimize the most significant variables in the treatment. As a result, the process removed 90.20% of the initial MeP after 120 minutes, using the concentrations of 25 mg/L of O3, 30 mg/L of H2O2 and in the pH of the effluent itself (7.0±2). The physicochemical parameters were improved and the acute toxicity of the effluent with compound for the bioindicator species Artemia salina was reduced, proving the wide efficiency of the employed POA. Keywords: AOPs; Ozone; Parabens.